Fatal Type B Lactic Acidosis Associated With Metastatic Colorectal Cancer: A Case Report With Review of Literature, Pathogenesis, and Treatment - Bharatsinh Gharia MD; Karan Seegobin MD; Hetavi Mahida MD; Marwan Shaikh MD; Trevanne Matthews Hew MD; Dat Pham MD (SAGE Publishing, 2018)
Type B lactic acidosis associated with malignancy is a life-threatening complication and mostly seen in hematological malignancies but can also be seen in solid tumors. We report a rare case of a 64-year-old female diagnosed with metastatic adenocarcinoma of the colon with liver metastasis associated with severe type B lactic acidosis. We discuss pathophysiology, previously reported cases, and their outcomes. The most widely used therapies are bicarbonate infusion, thiamine supplementation, chemotherapy, and supportive care but is associated with poor outcomes, and no standard treatment recommendations are available. Early chemotherapy administration remains the only intervention that has shown some survival benefit. Physicians should be aware and proactive for early diagnosis and management of this condition with further research needed to guide optimal therapy.